An internet-based information system for the sport scientific theory of selected sports disciplines - Baca, A.; Eder, C. (International Journal of Computer Science in Sport, 2002)
Throughout the last years sport-scientific information systems have been developed for several sports disciplines or for sub fields of sport science. Interdisciplinary approaches have been an exception, the development of multidisciplinary, comprehensive information systems shows a deficit. This deficit shall be reduced by a cooperative project between the Institutes of Sport Science of the Universities of Vienna and Salzburg. Based on four selected sport disciplines abstract theoretical concepts of sub fields of sport science will be presented interdisciplinary. Sports disciplines · Alpine Skiing · Tennis · Athletics (in particular running and jumping disciplines) · Soccer Sub fields · Sports Biomechanics · Sports Medicine and Exercise Physiology · Sports Psychology · Kinesiology · Applied Computer Science · Exercise Science Starting with a practical application - the sports discipline or the sports movement · the interest should be aroused in studying theoretical concepts more intensively and an understanding for complex connections should be obtained more rapidly · the interdisciplinary understanding in sport science should be improved both in research and education · a more economic and effective education should be achieved Applying a constructivist approach the critical, networked and holistic thinking should be stimulated. Based on selected practical examples the theoretical connections/overlappings of the sub fields will become transparent. Through the use of computer animations, video sequences and simulations not only high interactivity will be achieved, but also should the practical relevance of the theoretical concepts presented be underlined immediately. The total project period is two years. Since June, 2002 a prototype of the module "Alpine Skiing" is available. The end of the project is scheduled for the end of 2003.